Considerations in Forehead Reduction for Men - Núñez-Castañeda, José Miguel; Chang-Grozo, Silvana Lucia (Facial Plastic Surgery, 2023)
Although frontal prominence is an infrequent benign defect that causes no sequelae, it gives the patient distress due to its unaesthetic visual aspect. Proper surgical recontouring of the forehead can radically change one's appearance. In consequence, different techniques have been proposed for its management and correction. The aim of this study is to describe a surgical algorithm to treat male patients with forehead reduction to soften the “forceful” look. An observational cross-sectional study was conducted at the head and neck surgery ward of a general hospital between 2019 and 2022. We performed 35 forehead reduction operations on male patients. The median age was 29 years (range, 26–32 years). The forehead reduction procedures performed was categorized as follows: 27 anterior table osteotomy and 8 anterior table osteotomy contouring. Median forehead reduction was 2.7 mm (range, 2–3.2 mm). The average medical follow-up for patients was 6 months, with an interval ranging from 4 to 8 months. Surgery of the forehead in properly selected male patients is sufficiently safe that it can be done for entirely aesthetic reasons. The choice of surgical technique depends on the presence or absence of the pneumatized frontal sinus. If the frontal sinus is not pneumatized, an anterior table contouring is performed and if the frontal sinus is pneumatized, an anterior table osteotomy is preferred.
Keywords: forehead reduction; frontal prominence; surgical technique